2007
DOI: 10.1002/bdd.569
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of diclofenac in rats intoxicated with CCL4, and in the regenerating liver

Abstract: The pharmacokinetics of an intravenous and oral diclofenac dose of 3.2 mg/kg was studied in male Wistar rats under control conditions, 1 and 3 days after liver damage and regeneration induced by an oral injection of CCl(4). One day after CCl(4) administration, indicators of necrosis (alanine aminotransferase), cholestasis (gamma-glutamyl transpeptidase) and regeneration (alpha-fetoprotein) were significantly increased; these effects were reversed after 3 days. In nonintoxicated rats, t(1/2) was 43.83 +/- 4.95 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The minimal blood volume required for analysis (10 μl) (Section 3.1) enabled sample collection by serial bleeding without disturbing the fluid balance of the animals 37. Although whole blood was used in this analysis, the results were comparable to previous observations described for plasma 38,39. After i.p.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The minimal blood volume required for analysis (10 μl) (Section 3.1) enabled sample collection by serial bleeding without disturbing the fluid balance of the animals 37. Although whole blood was used in this analysis, the results were comparable to previous observations described for plasma 38,39. After i.p.…”
Section: Resultssupporting
confidence: 85%
“…This C max is consistent with the results from Reyes-Gordillo et al , who reported a plasma C max of about 1 μg mL −1 following i.v. administration of DCF at 3 mg kg −1 bodyweight 39. DCF is rapidly excreted, as described previously39 and after 2.4 h only half of the concentration remains in the blood.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Like the other NSAIDs, the mechanism of anti-inflammatory, analgesic and antipyretic action proceeds via the inhibition of the COX enzyme, which transforms arachidonic acid to prostaglandin, prostaeyelin and thromboxane (1,2). 'Please send reprint request to: Dr Zdenko Tomic, Institute of Pharmacology, Toxicology and Clinical Pharmacology, Faculty of Medicine, University of Novi Sad, Novi Sad, Serbia zdenkoto@eunet.rs Diclofenac is metabolized in the liver by the hydroxylation at the positions 3, 4 and 5 and conjugation with glucuronic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Diclofenac blood concentrations were estimated by HPLC by a procedure developed and validated in our laboratory. This method has been previously described in detail (21).…”
Section: Analysis Of Diclofenac In Bloodmentioning
confidence: 99%